(3NdGUI GdEXgGQs - (3GdOeTbj, Ydj Hf eMjj GdOjf, cGf MjG (B1310 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj de jJNP hdOG hde jcf dg TQjc aj edcg CeG HYO ajbhd Ydj GHf eMjj GdOjf GdOeTbj deG WGdYJ cJGH GdTjN GdeSei HdEXgGQ GdMb Gf CUfY cJGH hCPcQ ajg GdeSGFd GdNeS hSejJg NdGUI GdEXgGQs
(3BNQgG (B:s
(3ceG gh eUQM Hg aj GdHGH GdSGOS YTQ hGdHGH GdMGOj hYTQjf ef SaQ GdYOO adG GSJMGdI YbdG hfbdG aj chf eMeO Udi Gddg Ydjg hSde TajY GdePfHjfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds